Negative electrode, method for preparing negative electrode and battery

By coating the polymer layer containing inorganic compounds and polymers on the negative electrode of the semi-solid lithium/sodium metal battery, the problems of low capacity retention and short cycle life at low temperatures are solved, and efficient lithium/sodium ion transport and electrochemical performance improvements are achieved.

CN119481380BActive Publication Date: 2025-04-22SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510046734.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The negative electrode of the existing semi-solid lithium/sodium metal batteries has low capacity retention rate at low temperatures, short cycle life, and is prone to the problem of reduced lithium/sodium ion activity.

Method used

A polymer slurry prepared by polymerizing the first curing agent and the second curing agent in the presence of an initiator and an inorganic compound is coated on the negative electrode active material layer to form a polymer layer that is both flexible and rigid.

Benefits of technology

It improves the high ionic conductivity of the battery at low temperatures, extends the cycle life of the battery, enhances the electrochemical performance, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of semi-solid-state batteries, and in particular to a negative electrode, a method for preparing the negative electrode, and a battery. The present invention provides a negative electrode, the negative electrode comprising a current collector, a negative electrode active material layer disposed on the current collector, and a polymer layer disposed on the negative electrode active material layer on a side away from the current collector, the polymer layer comprising an inorganic compound and a polymer, the chemical formula of the inorganic compound being A x ‑B y F z , wherein x≥1, y≥1, z≥3, A is at least one of magnesium, aluminum, and zinc, B is at least one of lithium or sodium, and F is fluorine. x ‑B y F z Inorganic compounds can prevent cracks in the interface film due to changes in the volume of the negative electrode during use, extend the service life, improve the cycle performance, and at the same time increase the lithium / sodium ion transfer number, thereby significantly improving the electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid state batteries, and in particular to a negative electrode, a method for preparing the negative electrode, and a battery. Background Art

[0002] As people's quality of life improves, more and more non-renewable fossil energy with limited reserves is consumed in large quantities. In order to meet energy needs, the promotion and utilization of green energy is particularly important. Among many energy storage methods, lithium-ion batteries, as a portable energy storage system, occupy an extremely important position. However, most traditional liquid lithium-ion batteries use carbonates, ethers, esters and other toxic, flammable and volatile organic mixed electrolytes. When the temperature rises sharply during use, many thermal decomposition reactions will occur between the components of the organic liquid electrolyte in the battery, releasing a large amount of flammable gas and generating a large amount of energy, which will lead to fire and explosion. In order to improve the high energy density of lithium / sodium batteries while meeting safety requirements, semi-solid lithium / sodium metal batteries with better high-temperature stability, good mechanical properties and higher energy density have become one of the key systems of the next generation of lithium-ion batteries. The negative electrode of the semi-solid lithium / sodium metal battery directly affects the performance and cycle life of the battery. Among them, lithium / sodium metal materials have become the preferred choice for the negative electrode of semi-solid lithium / sodium metal batteries due to their high lithium / sodium ion energy storage and good specific capacity performance. However, since lithium / sodium metals have a high surface diffusion energy barrier, lithium / sodium metals are more inclined to aggregate and deposit at a certain site to form dendrites, which leads to a significant decrease in the activity of lithium / sodium ions.

[0003] Studies have shown that constructing a lithium fluoride / sodium solid electrolyte interface film on the surface of lithium / sodium metal can inhibit the growth of lithium dendrites. At present, most electrolytes using lithium bis(fluorosulfonyl)imide (LiFSI) / sodium bis(fluorosulfonyl)imide (NaFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) / sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) as raw materials form a lithium fluoride / sodium interface film on the negative electrode surface of the battery. However, organic fluorides are difficult to dissociate lithium fluoride / sodium fluoride at low temperatures, especially at -10°C, and the high crystallinity and heterogeneity of lithium carbonate / sodium will lead to the interfacial Li + / Na + Transport barriers accelerate the growth of lithium / sodium grafts, resulting in shortened battery cycle life and rapid capacity decay at low temperatures. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of short cycle life and rapid capacity decay at low temperatures in the prior art, thereby providing a negative electrode, a method for preparing the negative electrode and a battery.

[0005] Another technical problem to be solved by the present invention is to overcome the defect of low capacity retention rate in low temperature environment in the prior art, thereby providing a negative electrode, a method for preparing the negative electrode and a battery.

[0006] In one aspect, the present invention provides a negative electrode, the negative electrode comprising a current collector, a negative electrode active material layer disposed on the current collector, and a polymer layer disposed on a side of the negative electrode active material layer away from the current collector, the polymer layer comprising an inorganic compound and a polymer, the chemical formula of the inorganic compound is A x -B y F z , wherein x≥1, y≥1, z≥3, A is at least one of magnesium, aluminum, and zinc, B is at least one of lithium or sodium, and F is fluorine;

[0007] The polymer layer is made of a polymer slurry obtained by reacting a first curing agent and a second curing agent in the presence of an initiator and an inorganic compound;

[0008] The first curing agent has a structure shown in formula (I):

[0009]

[0010] Formula (I);

[0011] Wherein, R1, R2, R3, and R4 are independently selected from a group having a structure represented by formula (II) or formula (III) or a C1-C4 alkyl group, wherein at least one of R1, R2, R3, and R4 is selected from a group having a structure represented by formula (II) or formula (III):

[0012]

[0013] Formula (II);

[0014]

[0015] Formula (III);

[0016] In formula (II) or formula (III), n≥1;

[0017] The second curing agent has the structure described by formula (IV):

[0018]

[0019] Formula (IV);

[0020] wherein R5 is selected from a C1-C6 fluorinated alkyl group, R6 is selected from at least one of a C1-C4 alkyl group, a C1-C4 fluorinated alkyl group, and R7-C=O-, and R7 is selected from an unsubstituted or R m Substituted C1-C6 alkyl, unsubstituted or Rm At least one of the substituted C2-C6 alkenyl groups, R m It is F, C1-C3 alkyl.

[0021] In some embodiments, the initiator has a structure shown in formula (V):

[0022]

[0023] Formula (V);

[0024] Among them, R8, R9, R 10 , R 11 are independently selected from unsubstituted or R k Substituted C1-C4 alkyl, R k It is at least one of a C1-C3 alkoxy group or a C1-C3 alkyl group.

[0025] In some of the embodiments, in the inorganic compound, the value range of x is 1-5, the value range of y is 1-15, and the value range of z is 3-20.

[0026] In some of the embodiments, the value of n in the substituent of the structure represented by formula (II) or formula (III) is 1-10.

[0027] In some embodiments, in the second curing agent, R5 is selected from -CH2CF2CHFCF3, and R6 is selected from methyl, vinyl, isopropenyl, -CHFCH2F or -CH2F.

[0028] The mass ratio of the first curing agent to the second curing agent is (1-5): (1-5).

[0029] The molar concentration of the inorganic compound in the mixture formed by the first curing agent, the second curing agent and the inorganic compound is 0.1 mol / L to 1 mol / L.

[0030] The mass concentration of the initiator in the polymer slurry is 0.5% to 1%.

[0031] In some embodiments, the first curing agent is a compound with a CAS number of 28961-43-5, a compound with a CAS number of 75577-70-7, or a compound with a CAS number of 51728-26-8. The structural formula of the first curing agent is shown in Table 1.

[0032]

[0033] In some embodiments, the second curing agent is at least one of a compound with a CAS number of 36405-47-7, a compound with a CAS number of 64376-86-9, a compound with a CAS number of 104724-99-4, a compound with a CAS number of 131644-91-2, a compound with a CAS number of 54052-90-3, and a compound with a CAS number of 58705-93-4. The structural formula of the second curing agent is shown in Table 2.

[0034]

[0035] The initiator is at least one of a compound with a CAS number of 78-67-1, a compound with a CAS number of 13472-08-7, a compound with a CAS number of 4419-11-8, and a compound with a CAS number of 15545-97-8. The structural formula of the initiator is shown in Table 3.

[0036]

[0037] In some of the embodiments, the negative electrode active material layer is a carbon-based compound, a silicon-based compound, a titanium-based compound, an alloy material or a transition metal compound. Exemplarily, the material of the negative electrode active material layer can be graphite, graphene, hard carbon, soft carbon, silicon oxide, silicon carbon, silicon-based alloy, lithium, lithium titanate, tin dioxide or other negative electrode active materials.

[0038] In some of the embodiments, the current collector is copper foil or a composite material containing metal materials, such as a sandwich structure of "metal conductive layer-polymer composite material-metal conductive layer", with the outer two layers being copper metal and aluminum metal, and the middle body being a polymer material of polyethylene terephthalate (PET) or polypropylene (PP). This sandwich structure not only ensures the basic conductive function of the current collector, but also has a significant improvement in energy density, safety performance and material cost. The composite current collector uses a polymer layer made of plastic material, which greatly reduces the use of metal materials and the overall weight, and improves the performance and economy of the battery.

[0039] In some embodiments, the first curing agent and the second curing agent react in the presence of an initiator and an inorganic compound to prepare a polymer slurry at a reaction temperature of 20 to 55° C. and a reaction time of 30 seconds to 4 hours. More specifically, during the reaction, the higher the concentration of the reaction raw materials, the shorter the polymerization reaction time.

[0040] In some embodiments, the thickness of the polymer layer in the negative electrode is 200 nm-5 μm.

[0041] In another aspect, the present invention provides a method for preparing the negative electrode, comprising coating a polymer slurry containing an inorganic compound and a polymer on a current collector containing a negative electrode active material layer to form the negative electrode.

[0042] In some of the embodiments, the method for preparing the slurry containing the inorganic compound and the polymer comprises the following steps: S1, synthesizing the inorganic compound; S2, mixing the first fixing agent, the second fixing agent and the inorganic compound synthesized in step S1, adding an initiator thereto, and obtaining the slurry containing the inorganic compound and the polymer after the reaction.

[0043] In some of the embodiments, the method for synthesizing the inorganic compound in step S1 is to mix and heat-treat various raw materials to obtain the inorganic compound, and the raw materials include a B source, an F source, and an A source.

[0044] In some embodiments, in step S2, under stirring, the first fixing agent and the second fixing agent are mixed for a first time to form a first mixed solution, the inorganic compound synthesized in step S1 is added to the first mixed solution and mixed for a second time, and the initiator is added to the second mixed solution and mixed for a third time.

[0045] Among them, the stirring speed of the first fixing agent and the second fixing agent is 50 rpm ~200rpm, the first time is 10 min ~ 60min, the stirring speed of the first mixed solution and the inorganic compound is 75 rpm ~250rpm, the second time is 30min ~ 3h, and the stirring speed when the initiator is added to the second mixed solution is 100 rpm ~350rpm, and the third time is 30s ~ 30min.

[0046] In some of the embodiments, the step of mixing the raw materials in the synthesis of the inorganic compound is grinding the raw materials at a rotation speed of 150 rpm to 550 rpm for 2 h to 15 h.

[0047] In some embodiments, during the heat treatment in step S1, the temperature is increased to 100°C~350°C at a heating rate of 0.5°C / min~20°C / min, and then cooled to room temperature at a cooling rate of 0.5°C / min~5°C / min. The heat treatment time is 30min~6h.

[0048] In some of the embodiments, the F source is at least one of ammonium bifluoride, ammonium fluoride, sodium fluoride, lithium fluoride, magnesium fluoride, aluminum fluoride and zinc fluoride.

[0049] In some embodiments, the A source is at least one of a magnesium salt, a zinc salt or an aluminum salt.

[0050] Preferably, the magnesium salt is at least one of magnesium nitrate, magnesium acetate and magnesium fluoride.

[0051] Preferably, the aluminum salt is at least one of aluminum nitrate, aluminum phosphate and aluminum fluoride.

[0052] Preferably, the zinc salt is at least one of zinc nitrate, zinc acetate and zinc fluoride.

[0053] In some embodiments, the B source is at least one of a sodium salt and a lithium salt.

[0054] Preferably, the sodium source is at least one of sodium nitrate, sodium oxalate, sodium sulfate and sodium fluoride.

[0055] Preferably, the lithium source is at least one of lithium nitrate, lithium oxalate, lithium sulfate and lithium fluoride.

[0056] In some embodiments, the molar ratio of the B source to the F source and the A source is (1-15): (2-20): (1-5).

[0057] In some embodiments, the raw materials in the synthesis method of the inorganic compound are at least one of sodium fluoride or lithium fluoride and at least one of magnesium fluoride, aluminum fluoride, and zinc fluoride.

[0058] Preferably, the molar ratio of sodium fluoride / lithium fluoride to magnesium fluoride / aluminum fluoride / zinc fluoride is (1-15): (1-5).

[0059] In the synthesis of the inorganic compound, during the grinding process, a step of adding a dispersant to the mixture formed by the raw materials is also included, and the dispersant includes at least one of pyrrolidone, methylpyrrolidone, and N-methylpyrrolidone. The amount of the dispersant added is 0.5% to 30% of the total mass of the mixture formed by the raw materials in the synthesis of the inorganic compound.

[0060] When a dispersant is added to the mixture, before the heat treatment, the method further includes vacuum drying the ground mixed solution at 50° C. to 100° C. for 5 h to 16 h.

[0061] In some of the embodiments, the current collector containing the negative electrode active material layer is an electrode structure formed by coating the negative electrode active material on the upper and lower surfaces of the current collector. Exemplarily, the current collector can be a copper foil, the negative electrode active material can be lithium, the thickness of the copper foil is 5 to 10 μm, preferably 6 μm, and the thickness of the negative electrode active material coated on the upper or lower surface of the current collector is 15 to 25 μm, preferably 20 μm.

[0062] Meanwhile, the present invention also provides a battery, which comprises the above-mentioned negative electrode or the negative electrode prepared by the above-mentioned negative electrode preparation method.

[0063] In some embodiments, the battery further comprises a diaphragm, a surface of which is coated with at least one of a lithium lanthanum zirconium oxide solid electrolyte or a sodium lanthanum zirconium oxide solid electrolyte.

[0064] Preferably, the concentration of lithium salt or sodium salt in the electrolyte of the battery is greater than or equal to 1.8 mol / L, and preferably, the concentration of lithium salt or sodium salt in the electrolyte is greater than or equal to 2.5 mol / L.

[0065] The technical solution of the present invention has the following advantages:

[0066] 1. The present invention provides a negative electrode, the negative electrode comprising a current collector, a negative electrode active material layer disposed on the current collector, and a polymer layer disposed on the negative electrode active material layer away from the current collector, the polymer layer comprising an inorganic compound and a polymer, the chemical formula of the inorganic compound is A x -B y F z , wherein x≥1, y≥1, z≥3, A is at least one of magnesium, aluminum, and zinc, B is at least one of lithium or sodium, and F is fluorine; the polymer layer is formed by a first curing agent, a second curing agent, and a mixture of an inorganic compound in the presence of an initiator to obtain a polymer slurry through a polymerization reaction, the first curing agent having a structure as shown in formula (I), wherein R1, R2, R3, and R4 are independently selected from a group having a structure as shown in formula (II) or formula (III) or a C1-C4 alkyl group, wherein at least one of R1, R2, R3, and R4 is selected from a group having a structure as shown in formula (II) or formula (III), and n≥1 in the group having a structure as shown in formula (II) or formula (III); the second curing agent has a structure as shown in formula (IV), wherein R5 and R6 are independently selected from a C1-C6 fluorinated alkyl group, and the rest are at least one of a C1-C4 alkyl group, a C1-C4 fluorinated alkyl group, and R7-C=O-, and R7 is selected from an unsubstituted or R m Substituted C1-C6 alkyl, unsubstituted or R m At least one of the substituted C2-C6 alkenyl groups, R m It is F, C1-C3 alkyl.

[0067] The present invention utilizes the ethoxy chain ( ), which can provide longer flexible segments, and these flexible segments can make the cured material better adapt to stress, so that the interface film formed by the prepared polymer is flexible, and the second curing agent has a C1-C6 fluorinated alkyl group, which makes the interface film formed by the prepared polymer rigid. In the present invention, the unsaturated double bonds of the first curing agent and the second curing agent undergo cross-linking polymerization in the presence of an initiator to form a polymer with both flexibility and rigidity. At the same time, since the oxygen atom in the ester group or ether group of the second curing agent is a Lewis base and can provide a lone pair of electrons, the magnesium, aluminum or zinc atom in the inorganic compound forms a coordinate covalent bond with the lone pair of electrons in the second curing agent unit in the polymer to achieve the combination of the inorganic compound and the polymer, forming a polymer layer made of a polymer slurry containing an inorganic compound. The polymer not only contains a polymer that is both flexible and rigid, but more importantly, the polymer is also bonded to the inorganic compound through a coordinate covalent bond, which can avoid cracks in the interface film due to changes in the volume of the negative electrode during use, extend the service life, and improve the cycle performance. At the same time, the fluorinated chain segments in the polymer skeleton can synergistically weaken the coordination between lithium / sodium ions and the solvent, thereby achieving high ionic conductivity even at low temperatures.

[0068] In addition, the aluminum ions, magnesium ions, or zinc ions of inorganic compounds promote the lattice distortion and electron rearrangement of LiF, making A x -B y F z The activated lattice planes interact strongly with the polymer to release free F ions, thereby quickly producing a lithium fluoride or sodium fluoride-rich solid electrolyte interface film, which exhibits low Li + / Na + Diffusion barrier and high chemical stability; doping with aluminum ions, magnesium ions or zinc ions makes the LiF / NaF surface positively charged, which can accelerate the dissociation of lithium salt / sodium salt in high-concentration lithium salt / sodium salt electrolyte, limit the migration of lithium salt / sodium salt anions, and thus promote Li + / Na + The transmission of lithium / sodium ions can be increased, thereby significantly improving the electrochemical performance of the battery.

[0069] 2. The present invention provides a method for preparing a negative electrode, wherein a polymer slurry comprising an inorganic compound and a polymer is coated on a current collector comprising a negative electrode active material layer to form a negative electrode. The negative electrode preparation method provided by the present invention has a simple process and is easy to operate.

[0070] 3. A method for preparing a negative electrode provided by the present invention, the method for preparing a slurry containing an inorganic compound and a polymer, comprising the following steps: S1, synthesizing an inorganic compound; S2, mixing a first fixing agent, a second fixing agent and the inorganic compound synthesized in step S1, and adding an initiator thereto to obtain a slurry containing an inorganic compound and a polymer. Using the principle of coordinated covalent bonds, the magnesium, aluminum or zinc atoms in the inorganic compound of the present invention are combined with the second curing agent in the polymer, and the first curing agent and the second curing agent are polymerized by the initiator to form a slurry containing the inorganic compound A. x -B y F z and a polymer slurry of a polymer, the slurry forming a polymer layer on the negative electrode active material layer.

[0071] 4. A battery provided by the present invention comprises the above-mentioned negative electrode and a diaphragm, wherein the surface of the diaphragm is coated with a lithium lanthanum zirconium oxide / sodium lanthanum zirconium oxide solid electrolyte. Since the surface of lithium lanthanum zirconium oxide / sodium lanthanum zirconium oxide is highly alkaline, it is easy to react with H2O and CO2 in the air to form lithium carbonate (Li2CO3) / sodium carbonate layer (Na2CO3). The highly crystalline and heterogeneous lithium carbonate / sodium layer will cause the interface Li + / Na + The transport transfer is deteriorated, the dendrite growth is accelerated, and the Li2CO3 / Na2CO3 lithium / sodium ion conductivity is low, which will seriously hinder the ability of lithium / sodium ions to penetrate the diaphragm, causing battery failure. The present invention utilizes A in the slurry containing inorganic compounds and polymers x -B y F z The fluorine-containing components released by decomposition can, on the one hand, replace the anions in the lithium lanthanum zirconium oxide / sodium lanthanum zirconium oxide grains at high temperature. Since F has a higher electronegativity than O, the cation-anion chemical bond is strengthened, which restrains the movement of electrons and inhibits electronic conductivity. At the same time, the Li-O bond is strengthened, resulting in Li + / Na + The exchange capacity with protons in the air is reduced, which enhances its air stability; on the other hand, A x -B y F z Decomposition leaves AlF3, Al2O3 or MgF2, MgO or ZnF2, ZnO or even lithium / sodium fluoride in the grain boundaries, thus modifying the lithium lanthanum zirconium oxide / sodium lanthanum zirconium oxide grain boundaries and improving the electrochemical performance of the battery.

[0072] 5. A battery provided by the present invention, wherein the concentration of lithium salt or sodium salt in the electrolyte of the battery is greater than or equal to 1.8 M. The electrolyte containing high concentration of lithium salt or sodium salt will change the composition and structure of the interface film during the operation of the battery, affecting the protective effect and ion transmission performance of the interface film. The electrolyte containing high concentration of lithium salt or sodium salt will promote side reactions between the electrolyte and the electrode, resulting in loss of battery capacity. During the operation of the battery provided by the present invention, the negative electrode can quickly produce a LiF / NaF-rich interface film, which exhibits strong stability. At the same time, the LiF / NaF surface produced by the negative electrode is positively charged due to the doping of active metal ions, which can accelerate the dissociation of cations in the lithium salt or sodium salt in the electrolyte, limit the migration of anions, thereby promoting the transmission of lithium ions and sodium ions, and increasing the migration number of cations. Therefore, the battery provided by the present invention has good electrochemical performance in the electrolyte of high concentration of lithium salt or sodium salt. DETAILED DESCRIPTION

[0073] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0074] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0075] Preparation Example 1

[0076] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound, and the specific steps and methods are as follows:

[0077] (1) Synthesis of Al-LiF4: Aluminum nitrate, lithium nitrate and ammonium bifluoride were ground at a molar ratio of 1:1:2 at 300 rpm for 12 h to obtain a first mixture, the temperature was increased to 200°C at a heating rate of 10°C / min, the first mixed solution was treated at 200°C for 1 h, and the temperature was reduced to room temperature at a cooling rate of 2°C / min to obtain an inorganic compound Al-LiF4.

[0078] (2) Synthesis of a polymer rich in Al-LiF4: The first curing agent and the second curing agent were mixed at a mass ratio of 1:1 at 150 rpm for 30 min, the inorganic compound Al-LiF4 obtained in step (1) was added thereto, and the final concentration of the inorganic compound was 0.5 mol / L. The above materials were stirred at 200 rpm for 1 h to obtain a second mixed solution, an initiator was added to the second mixed solution, and the amount of the initiator added was 0.5 wt% of the second mixed solution. The mixture was stirred at 200 rpm for 1 min at 30° C. to obtain a polymer slurry containing an inorganic compound, wherein the first curing agent was a compound with a CAS number of 28961-43-5, the second curing agent was a compound with a CAS number of 36405-47-7, and the initiator was a compound with a CAS number of 78-67-1.

[0079] Preparation Example 2

[0080] This preparation example provides a preparation method of a polymer slurry containing an inorganic compound. The specific steps and method are the same as those of Preparation Example 1, except that the raw materials in step (1) are lithium fluoride and aluminum fluoride. The specific steps are: (1) Synthesis of Al-LiF4: according to the molar ratio of lithium fluoride to aluminum fluoride being 1:1, lithium fluoride and aluminum fluoride are ground at a rotation speed of 300 rpm for 12 hours to obtain a first mixed solution, the temperature is increased to 200°C at a heating rate of 10°C / min, the first mixed solution is treated at 200°C for 1 hour, and the temperature is reduced to room temperature at a cooling rate of 2°C / min to obtain the inorganic compound Al-LiF4.

[0081] Preparation Example 3

[0082] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 75577-70-7 is used to replace the compound with a CAS number of 28961-43-5 in step (2) as the first curing agent.

[0083] Preparation Example 4

[0084] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 51728-26-8 is used to replace the compound with a CAS number of 28961-43-5 in step (2) as the first curing agent.

[0085] Preparation Example 5

[0086] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 64376-86-9 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent.

[0087] Preparation Example 6

[0088] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 104724-99-4 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent.

[0089] Preparation Example 7

[0090] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 131644-91-2 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent.

[0091] Preparation Example 8

[0092] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 54052-90-3 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent.

[0093] Preparation Example 9

[0094] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound. The specific steps and methods are the same as those of Preparation Example 1, except that an equal mass of a compound with a CAS number of 58705-93-4 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent.

[0095] Preparation Example 10

[0096] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound, and the specific steps and methods are as follows:

[0097] (1) Synthesis of Al2-LiF7: Aluminum phosphate, lithium oxalate and ammonium fluoride were ground at a rotation speed of 150 rpm for 15 h in a molar ratio of 4:1:14 to obtain a first mixed solution. The temperature was increased to 100°C at a heating rate of 0.5°C / min, the first mixed solution was treated at 100°C for 6 h, and the temperature was reduced to room temperature at a cooling rate of 0.5°C / min to obtain an inorganic compound Al2-LiF4.

[0098] (2) Synthesis of a polymer rich in Al2-LiF7: The first fixative and the second fixative are mixed at a mass ratio of 1:5 at 200 rpm for 10 min, the inorganic compound Al2-LiF4 obtained in step (1) is added thereto, and the final concentration of the inorganic compound is 1.0 mol / L. The above materials are stirred at 75 rpm for 3 h to obtain a second mixed solution, an initiator is added to the second mixed solution, the amount of the initiator added is 1.0 wt% of the second mixed solution, and the mixture is stirred at 100 rpm for 5 min to obtain a polymer slurry containing an inorganic compound, wherein the first fixative is a compound with a CAS number of 28961-43-5, the second fixative is a compound with a CAS number of 36405-47-7, and the initiator is a compound with a CAS number of 15545-97-8.

[0099] Preparation Example 11

[0100] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound, and the specific steps and methods are as follows:

[0101] (1) Synthesis of Mg-Li2F4: According to the molar ratio of magnesium nitrate, lithium sulfate and ammonium bifluoride of 1:1:2, magnesium nitrate, lithium sulfate and ammonium bifluoride were ground at 550 rpm for 2 hours to obtain a first mixed solution, the temperature was increased to 350°C at a heating rate of 20°C / min, the first mixed solution was treated at 350°C for 30 minutes, and the temperature was reduced to room temperature at a cooling rate of 5°C / min to obtain an inorganic compound Mg-Li2F4.

[0102] (2) Synthesis of a polymer rich in Mg-Li2F4: The first curing agent and the second curing agent are mixed at a mass ratio of 5:1 at 50 rpm for 60 min, and the inorganic compound Mg-Li2F4 obtained in step (1) is added thereto, and the final concentration of the inorganic compound is 0.1 mol / L. The above materials are stirred at 250 rpm for 30 min to obtain a second mixed solution, and an initiator is added to the second mixed solution, and the amount of the initiator added is 0.5 wt% of the second mixed solution. The mixture is stirred at 350 rpm for 30 s to obtain a polymer slurry containing an inorganic compound, wherein the first curing agent is a compound with a CAS number of 28961-43-5, the second curing agent is a compound with a CAS number of 36405-47-7, and the initiator is a compound with a CAS number of 13472-08-7.

[0103] Preparation Example 12

[0104] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound, and the specific steps and methods are as follows:

[0105] (1) Synthesis of Mg-LiF3: According to the molar ratio of magnesium acetate, lithium nitrate and ammonium bifluoride being 3:3:4.5, magnesium acetate, lithium nitrate and ammonium bifluoride are ground at 300 rpm for 12 hours to obtain a first mixture, the temperature is increased to 200°C at a heating rate of 10°C / min, the first mixed solution is treated at 200°C for 1 hour, and the temperature is reduced to room temperature at a cooling rate of 2°C / min to obtain an inorganic compound Mg-LiF3.

[0106] (2) Synthesis of a polymer rich in Mg3-Li3F9: The first curing agent and the second curing agent were mixed at a mass ratio of 1:1 at 150 rpm for 30 min, and the inorganic compound Mg3-Li3F9 obtained in step (1) was added thereto, with the final concentration of the inorganic compound being 0.5 mol / L. The above materials were stirred at 200 rpm for 1 h to obtain a second mixed solution, and an initiator was added to the second mixed solution, with the amount of the initiator added being 0.5 wt% of the second mixed solution. The stirring was continued for 1 min to obtain a polymer slurry containing the inorganic compound, wherein the first curing agent was a compound with a CAS number of 28961-43-5, the second curing agent was a compound with a CAS number of 36405-47-7, and the initiator was a compound with a CAS number of 4419-11-8.

[0107] Preparation Example 13

[0108] This preparation example provides a method for preparing a polymer slurry containing an inorganic compound, and the specific steps and methods are as follows:

[0109] (1) Mg-Li 15 F 17 Synthesis: According to the molar ratio of magnesium fluoride to lithium fluoride of 1:15, magnesium fluoride and lithium fluoride are ground at a speed of 300 rpm for 12 hours. During the grinding process, N-methylpyrrolidone is added thereto, and the amount of N-methylpyrrolidone added is 5wt% of the total mass of magnesium fluoride and lithium fluoride to obtain a first mixed solution. The first mixed solution is dried at 80°C under vacuum conditions for 5 hours to obtain a first mixture. The temperature of the first mixture is increased to 200°C at a heating rate of 10°C / min, the first mixed solution is treated at 200°C for 1 hour, and the temperature is reduced to room temperature at a cooling rate of 2°C / min to obtain an inorganic compound Mg-Li 15 F 17 .

[0110] (2) Rich in Mg-Li 15 F 17 Synthesis of the polymer: According to the mass ratio of the first fixative to the second fixative of 1:1, the first fixative and the second fixative were mixed at a speed of 150 rpm for 30 minutes, and the inorganic compound Mg-Li obtained in step (1) was added thereto. 15 F 17 , the final concentration of the inorganic compound is 0.5 mol / L, the above materials are stirred at a speed of 200 rpm for 1 hour to obtain a second mixed solution, an initiator is added to the second mixed solution, the amount of the initiator added is 0.5 wt% of the second mixed solution, and the mixture is stirred at a speed of 200 rpm for 1 minute to obtain a polymer slurry containing an inorganic compound, wherein the first fixing agent is a compound with a CAS number of 28961-43-5, the second fixing agent is a compound with a CAS number of 36405-47-7, and the initiator is a compound with a CAS number of 78-67-1.

[0111] Preparation Example 14

[0112] This preparation example provides a method for preparing a slurry containing an inorganic compound and a polymer. The specific steps and methods are the same as those of Preparation Example 13, except that pyrrolidone is used to replace N-methylpyrrolidone in step (1), the amount of pyrrolidone added is 0.5wt% of the total mass of magnesium fluoride and lithium fluoride, and the vacuum drying temperature is 50°C and the drying time is 16h.

[0113] Preparation Example 15

[0114] This preparation example provides a method for preparing a slurry containing an inorganic compound and a polymer. The specific steps and methods are the same as those of Preparation Example 13, except that methyl pyrrolidone is used to replace the N-methyl pyrrolidone in step (1), the amount of pyrrolidone added is 30 wt% of the total mass of magnesium fluoride and lithium fluoride, the vacuum drying temperature is 100°C, and the drying time is 10 h.

[0115] Preparation Example 16

[0116] This preparation example provides a method for preparing a slurry containing an inorganic compound and a polymer. The specific steps and methods are the same as those in Preparation Example 1, except that an equimolar amount of sodium nitrate is used to replace the lithium nitrate in step (1).

[0117] Example 1

[0118] This embodiment provides a series of negative electrode preparation methods, and the specific steps and parameters are as follows:

[0119] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0120] (2) A coating machine is used to coat the polymer slurry containing inorganic compounds obtained in Preparation Example 1 of the present invention onto the upper and lower lithium metal surfaces of the copper-lithium composite tape, and after heating and drying at 35°C, a polymer layer is formed on each side of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0121] Example 2-Example 16

[0122] The preparation method of the negative electrode is basically the same as that of Example 1, except that the polymer slurry containing inorganic compounds prepared in Preparation Examples 2-16 is used to replace the polymer slurry containing inorganic compounds prepared in Preparation Example 1 in step (2) of Example 1.

[0123] Comparative Example 1

[0124] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0125] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0126] (2) Mixing the inorganic compound Al-LiF4 powder obtained in step (1) of Preparation Example 1 with tetrahydrofuran solvent to obtain a solution with an inorganic compound concentration of 0.3 M;

[0127] The solution was coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip using a coating machine, and after heating and drying at 60°C, an inorganic compound layer was formed on both sides of the current collector. The single-sided thickness of the inorganic compound layer was 500nm, and a negative electrode was obtained.

[0128] Comparative Example 2

[0129] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0130] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0131] (2) A solution containing lithium bis(fluorosulfonyl)imide (LiFSI) is coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip by a coating machine, and a polymer layer is formed on each side of the current collector after heating and drying at 35°C. The single-sided thickness of the polymer layer is 500nmXX, thereby obtaining a negative electrode. The concentration of LiFSI in the solution containing lithium bis(fluorosulfonyl)imide is 0.5 mol, and the solvent of the solution containing lithium bis(fluorosulfonyl)imide is N,N-dimethylformamide.

[0132] Comparative Example 3

[0133] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0134] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0135] (2) A coating machine is used to coat the polymer slurry onto the upper and lower lithium metal surfaces of the copper-lithium composite strip. After heating and drying at 35°C, a polymer layer is formed on both sides of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0136] Preparation method of polymer slurry: according to the mass ratio of the first curing agent to the second curing agent of 1:1, the first fixing agent and the second fixing agent are mixed at a speed of 150 rpm for 30 minutes to obtain a mixed solution, an initiator is added to the mixed solution, the amount of the initiator added is 0.5wt% of the mixed solution, and the mixture is stirred at a speed of 200 rpm for 1 minute to obtain a polymer slurry, wherein the first fixing agent is a compound with a CAS number of 28961-43-5, the second fixing agent is a compound with a CAS number of 36405-47-7, and the initiator is a compound with a CAS number of 78-67-1.

[0137] Comparative Example 4

[0138] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0139] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0140] (2) A polymer slurry containing an inorganic compound is coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip using a coating machine. After heating and drying at 35°C, a polymer layer is formed on both sides of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0141] The preparation method of the polymer slurry containing inorganic compounds is the same as that of Preparation Example 1, except that an equal mass of hydroxyethyl acrylate is used to replace the first curing agent, and an equal mass of tetrafluoroethylene is used to replace the second curing agent to prepare a slurry containing inorganic compounds and polymers.

[0142] Comparative Example 5

[0143] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0144] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0145] (2) A polymer slurry containing an inorganic compound is coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip using a coating machine. After heating and drying at 35°C, a polymer layer is formed on both sides of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0146] The preparation method of the polymer slurry containing inorganic compounds is the same as that of Preparation Example 1, except that an equal mass of aniline is used to replace the first curing agent, and an equal mass of vinylidene fluoride is used to replace the second curing agent to prepare the polymer slurry containing inorganic compounds.

[0147] Comparative Example 6

[0148] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0149] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0150] (2) A polymer slurry containing an inorganic compound is coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip using a coating machine. After heating and drying at 35°C, a polymer layer is formed on both sides of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0151] The preparation method of the polymer slurry containing inorganic compounds is the same as that in Preparation Example 1, except that an equal mass of a compound with a CAS number of 28961-43-5 is used to replace the compound with a CAS number of 36405-47-7 in step (2) as the second curing agent, that is, a single curing agent is used to synthesize the polymer to obtain a slurry of the polymer containing inorganic compounds.

[0152] Comparative Example 7

[0153] This comparative example provides a method for preparing a negative electrode, and the specific steps and parameters are as follows:

[0154] (1) A 6 μm thick copper foil is selected, and lithium is coated on the upper and lower surfaces of the copper foil to form a copper-lithium composite strip, wherein the thickness of the lithium on the upper and lower surfaces is 20 μm.

[0155] (2) A polymer slurry containing an inorganic compound is coated onto the upper and lower lithium metal surfaces of the copper-lithium composite strip using a coating machine. After heating and drying at 35°C, a polymer layer is formed on both sides of the current collector. The single-sided thickness of the polymer layer is 500 nm, thereby obtaining a negative electrode.

[0156] The preparation method of the polymer slurry containing inorganic compounds is the same as that in Preparation Example 1, except that an equal mass of a compound with a CAS number of 36405-47-7 is used to replace the compound with a CAS number of 28961-43-5 in step (2) as the first curing agent, that is, a single curing agent is used to synthesize the polymer to obtain a slurry of the polymer containing inorganic compounds.

[0157] Application Example 1~Application Example 23

[0158] This application example provides a series of battery preparation methods. The specific steps and parameters are as follows:

[0159] In the presence of an organic solvent, N-methylpyrrolidone, lithium cobalt oxide, a conductive agent, PVDF, and carbon nanotubes (CNT) are mixed uniformly at a mass ratio of 97:1.5:1.0:0.5 to prepare a lithium-ion battery positive electrode slurry with a viscosity of 6500 mPa·s, which is then coated on an aluminum foil for a current collector, dried at 85°C, and cold pressed; then trimmed, cut, and slit, and then dried at 85°C for 8 hours under vacuum to prepare a positive electrode sheet that meets the requirements.

[0160] The positive electrode sheet, the negative electrode sheet and the lithium lanthanum zirconium oxide separator (including the base film and the lanthanum zirconium oxide coating on both sides of the base film, the base film material is polypropylene, the thickness is 9μm, and the molecular formula of lithium lanthanum zirconium oxide is Li7La3Zr2O 12, thickness 2μm) was made into a lithium metal battery with four positive plates and five negative plates through a lamination process with a capacity of 3000mAh. The electrolyte was injected. The electrolyte formula was to dissolve lithium bis(fluorosulfonyl)imide (LiFSI) in a mixture of ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE). The volume ratio of DME and TTE was 3:7, and the final concentration of LiFSI in the electrolyte was 2.5M. The soft-pack lithium metal battery was completed.

[0161] Among them, the negative electrodes prepared in Examples 1-15 and Comparative Examples 1-7 and the copper-lithium composite tape provided in step (1) of Example 1 are used as the negative electrode sheets in the batteries of Application Examples 1 to 23, and lithium metal batteries are prepared according to the above method.

[0162] Application Example 24

[0163] This application example provides a series of battery preparation methods. The specific steps and parameters are as follows:

[0164] In the presence of an organic solvent, N-methylpyrrolidone, sodium cobaltate, a conductive agent, PVDF, and carbon nanotubes (CNT) were mixed uniformly at a mass ratio of 97:1.5:1.0:0.5 to prepare a sodium ion battery positive electrode slurry with a viscosity of 6500 mPa·s, which was then coated on an aluminum foil for a current collector, dried at 85°C, and cold pressed; then trimmed, cut, and slit, and then dried at 85°C for 8 hours under vacuum to prepare a positive electrode sheet that met the requirements.

[0165] The positive electrode sheet, the negative electrode sheet and the sodium lanthanum zirconium oxide separator (including the base film and the lanthanum zirconium oxide coating on both sides of the base film, the base film material is polypropylene, the thickness is 9μm, and the molecular formula of lithium lanthanum zirconium oxide is Na7La3Zr2O 12 , thickness 2μm) was made into a lithium metal battery with four positive plates and five negative plates through a lamination process with a capacity of 3000mAh. The electrolyte was injected. The electrolyte formula was to dissolve sodium bis(fluorosulfonyl)imide (NaFSI) in a mixture of ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE). The volume ratio of DME and TTE was 3:7, and the final concentration of NaFSI was 2.5M. The soft-pack lithium metal battery was completed.

[0166] Among them, the negative electrode prepared in Example 16 was used as the negative electrode sheet in the battery of this application example, and a lithium metal battery was prepared according to the above method.

[0167] Application Example 25

[0168] This application example provides a method for preparing a battery. The specific steps and parameters are the same as those of Application Example 1, except that the concentration of bis(fluorosulfonyl)imide lithium salt in the electrolyte is 1.8 mol / L.

[0169] Test Case

[0170] The first efficiency, capacity retention rate after 100 cycles and average coulombic efficiency after 100 cycles of the batteries prepared in Application Examples 1 to 25 were measured at 25±5°C and -25±5°C. The results are shown in Table 4.

[0171] Table 4 Battery cycle test results

[0172]

[0173] Among them, the determination method of the first effect is: at 25±3℃, charge at a constant current of 0.1C to 4.2V, charge at a constant voltage of 4.2V to a cut-off current of 0.05C, record the charging capacity as C1, then discharge the battery at a constant current of 0.1C to 2.8V, and record the discharge capacity as D1; ​​first effect = (D1 / C1)×100%.

[0174] Method for determining the capacity retention rate after 100 cycles: At 25±3℃, charge to 4.2V at a constant current of 0.33C, charge to a cut-off current of 0.05C at a constant voltage of 4.2V, and then discharge the battery to 2.8V at a constant current of 1C. The discharge capacity is recorded as C1. Repeat the charge and discharge steps for 100 cycles to obtain the Nth cycle discharge capacity CN. The capacity retention rate at the 100th cycle = (CN / C1) × 100%.

[0175] Method for determining the average coulombic efficiency after 100 cycles: The test steps are the same as the test steps in the method for determining the capacity retention rate after 100 cycles. The calculation method is as follows: the coulombic efficiency of each cycle CE = discharge capacity / charge capacity × 100%, the average coulombic efficiency of n cycles CE = SUM (CE1~CEn) / n×100%, and SUM means sum.

[0176] Low temperature capacity retention rate test method: at 25±3℃, charge to 4.2V at 0.33C constant current, charge to a cut-off current of 0.05C at 4.2V constant voltage, and then discharge the battery to 2.8V at 0.5C constant current, and record the discharge capacity as D1; ​​at 25±3℃, charge to 4.2V at 0.33C constant current, charge to a cut-off current of 0.05C at 4.2V constant voltage, and after fully charged, adjust the temperature of the thermostat to the required low temperature state (the temperatures are -10℃, -25℃ and -35℃ respectively), start the discharge process after the temperature stabilizes, discharge the battery to 2.8V at 0.5C constant current, and record the discharge capacity as D2; low temperature capacity retention rate = (D2 / D1)×100%.

[0177] In this test example, the test is stopped when the cycle test capacity retention rate of the soft-pack lithium metal battery is lower than 80% and the coulomb efficiency is lower than 98%.

[0178] According to the test results in Table 1, compared with Comparative Examples 1-3 and the uncoated A-rich x -Li y F z The polymer layer copper-lithium composite belt, the battery formed by the negative electrode provided by the embodiment of the present invention has a high ratio of actual capacity to theoretical capacity during the first charge and discharge process, reaching more than 90%, and performs well in cycle capacity retention rate and average coulomb efficiency, proving that the negative electrode provided by the present invention can improve the cycle stability of the battery and extend the service life of the battery. Compared with Comparative Examples 4-7, the negative electrode formed by using two conventional curing agents or only a single curing agent as the raw material of the polymer, the present invention uses a slurry containing an inorganic compound and a polymer prepared by a specific first curing agent and a specific second curing agent. The polymer and the inorganic compound work synergistically, so that the prepared battery can also achieve high ionization conductivity at low temperatures.

[0179] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A negative electrode, characterized in that: The negative electrode comprises a current collector, a negative electrode active material layer disposed on the current collector, and a polymer layer disposed on a side of the negative electrode active material layer away from the current collector, wherein the polymer layer comprises an inorganic compound and a polymer, wherein the chemical formula of the inorganic compound is A x -B y F z , wherein x≥1, y≥1, z≥3, A is at least one of magnesium, aluminum or zinc, B is at least one of lithium or sodium, and F is fluorine; The polymer layer is made of a polymer slurry obtained by reacting a first curing agent and a second curing agent in the presence of an initiator and an inorganic compound; The first curing agent has a structure shown in formula (I): Formula (I); Wherein, R1, R2, R3, and R4 are independently selected from a group having a structure represented by formula (II) or formula (III) or a C1-C4 alkyl group, wherein at least one of R1, R2, R3, and R4 is selected from a group having a structure represented by formula (II) or formula (III): Formula (II); Formula (III); In formula (II) or formula (III), n≥1; The second curing agent has the structure described by formula (IV): Formula (IV); wherein R5 is selected from a C1-C6 fluorinated alkyl group, R6 is selected from at least one of a C1-C4 alkyl group, a C1-C4 fluorinated alkyl group, and R7-C=O-, and R7 is selected from an unsubstituted or R m Substituted C1-C6 alkyl, unsubstituted or R m At least one of the substituted C2-C6 alkenyl groups, R m It is F, C1-C3 alkyl.

2. The negative electrode according to claim 1, characterized in that The initiator has a structure shown in formula (V): Formula (V); Among them, R8, R9, R 10 , R 11 are independently selected from unsubstituted or R k Substituted C1-C4 alkyl, R k is at least one of a C1-C3 alkoxy group or a C1-C3 alkyl group; and / or, In the inorganic compound, the value range of x is 1-5, the value range of y is 1-15, and the value range of z is 3-20; and / or, The value of n in the substituent of the structure represented by formula (II) or formula (III) is 1 to 10; and / or, In the second curing agent, R5 is selected from -CH2CF2CHFCF3, and R6 is selected from methyl, vinyl, isopropenyl, -CHFCH2F or -CH2F.

3. The negative electrode according to claim 1, characterized in that The mass ratio of the first curing agent to the second curing agent is (1-5): (1-5); and / or, The molar concentration of the inorganic compound in the mixture formed by the first curing agent, the second curing agent and the inorganic compound is 0.1 mol / L to 1 mol / L; and / or, The mass concentration of the initiator in the polymer slurry is 0.5% to 1%; and / or, The first curing agent is at least one of a compound with a CAS number of 28961-43-5, a compound with a CAS number of 75577-70-7, and a compound with a CAS number of 51728-26-8; and / or, The second curing agent is at least one of a compound with a CAS number of 36405-47-7, a compound with a CAS number of 64376-86-9, a compound with a CAS number of 104724-99-4, a compound with a CAS number of 131644-91-2, a compound with a CAS number of 54052-90-3, and a compound with a CAS number of 58705-93-4; and / or, The initiator is at least one of a compound with a CAS number of 78-67-1, a compound with a CAS number of 13472-08-7, a compound with a CAS number of 4419-11-8, and a compound with a CAS number of 15545-97-8.

4. A method for preparing a negative electrode according to any one of claims 1 to 3, characterized in that: Applying a polymer slurry containing an inorganic compound and a polymer on a current collector containing a negative electrode active material layer to form a negative electrode; The method for preparing the slurry containing an inorganic compound and a polymer comprises the following steps: S1, synthesis of inorganic compounds; S2, mixing the first fixing agent, the second fixing agent and the inorganic compound synthesized in step S1, adding an initiator thereto, and obtaining a slurry containing the inorganic compound and the polymer after reaction; The method for synthesizing the inorganic compound in step S1 is to mix and heat-treat various raw materials to obtain the inorganic compound. The raw materials include B source, F source and A source; In step S2, under stirring, the first fixing agent and the second fixing agent are mixed for a first time to form a first mixed solution, the inorganic compound synthesized in step S1 is added to the first mixed solution and mixed for a second time, and the initiator is added to the second mixed solution and mixed for a third time.

5. The method for preparing a negative electrode according to claim 4, characterized in that: The stirring speed of the first fixing agent and the second fixing agent is 50 rpm ~200rpm, the first time is 10 min ~ 60min, the stirring speed of the first mixed solution and the inorganic compound is 75 rpm ~250rpm, the second time is 30min ~ 3h, and the stirring speed when the initiator is added to the second mixed solution is 100rpm ~350rpm, and the third time is 30s ~ 30min.

6. The method for preparing a negative electrode according to claim 5, characterized in that: The step of mixing the raw materials in the synthesis of the inorganic compound is grinding the raw materials at a rotation speed of 150 rpm to 550 rpm for 2 h to 15 h; and / or, During the heat treatment in step S1, the temperature is raised to 100°C to 350°C at a heating rate of 0.5°C / min to 20°C / min, and the temperature is lowered at a cooling rate of 0.5°C / min to 5°C / min, and the heat treatment time is 30min to 6h; and / or, The F source is at least one of ammonium bifluoride, ammonium fluoride, sodium fluoride, lithium fluoride, magnesium fluoride, aluminum fluoride and zinc fluoride; and / or, The A source is at least one of a magnesium salt, a zinc salt or an aluminum salt; and / or, The B source is at least one of a sodium salt and a lithium salt.

7. The method for preparing a negative electrode according to claim 6, characterized in that: The molar ratio of the B source, the F source and the A source is (1-15): (2-20): (1-5); and / or, The synthesis of the inorganic compound further includes a step of adding a dispersant to the mixture of the raw materials during the grinding process.

8. A battery, characterized in that: The invention comprises the negative electrode according to any one of claims 1 to 3 or the negative electrode prepared by the method for preparing the negative electrode according to any one of claims 4 to 7.

9. The battery according to claim 8, characterized in that It also includes a diaphragm, the surface of which is coated with at least one of a lithium lanthanum zirconium oxide solid electrolyte or a sodium lanthanum zirconium oxide solid electrolyte; and / or, The concentration of lithium salt or sodium salt in the electrolyte of the battery is greater than or equal to 1.8 mol / L.

Citation Information

Patent Citations

  • Solid-state lithium ion battery and preparation method thereof

    CN113130895A

  • In-situ polymerization solid-state battery with multi-layer structure electrolyte and preparation method of in-situ polymerization solid-state battery

    CN114335716A